DETERMINAN RETURN SAHAM: JAKARTA ISLAMIC INDEX VS LQ 45 - Dian Anggraini, Eka Ajeng; Pratomo, Ahmad Sidi (Faculty of Economics Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
The aims of this research are to know the influence of modal structure, systematical risk, and liquidity to the contribution return that is done by differentiating two indexes; Jakarta Islamic Index (JII) and Liquid 45 (LQ45). This research is a qualitative research which takes the samples in the companies that is listed in JII and LQ45 period 2014-2016. The total samples are 33 companies by using purposive sampling method. In doing the analysis, this research is using a doubled regression method and balance test by using SPSS 21 program. The result of this research shows that the variable of systematic risk of JII and LQ45 indexes have a significant influence to the contribution return. However, the variable of the financial capital and liquidity of JII and LQ45 indexes does not have a significant influence to the contribution return. In the result of balance test, there is a significant difference in the variable of modal structure in JII and LQ45. Here, the different result will show that there are no significant differences between the variables of systematical risk, liquidity, and contribution return in JII and LQ45.